MATHEMATICAL REASONING ABILITY OF STUDENTS AT SMA NEGERI 1 BELINYU ON THREE-DIMENSIONAL GEOMETRY - Alfiahni, Sri; Harfiyani (CV. Doki Course and Training, 2025)
This study aims to analyze the mathematical reasoning ability of 12th-grade students at SMA Negeri 1 Belinyu on three-dimensional geometry. Using a quantitative descriptive method, data were collected through essay tests and interviews. Results showed that students had moderate mathematical reasoning ability, with an average score of 47.14%. Among four measured indicators, students performed best in presenting mathematical statements (65.83%) and constructing proofs (61.39%), but poorly in identifying patterns (38.33%) and drawing conclusions (16.39%). These findings indicate the need for instructional strategies that emphasize critical thinking and structured reasoning. This research contributes to understanding students’ difficulties in spatial reasoning and supports curriculum development for geometry learning.